Tingkat Pengetahuan Pasien terhadap Penggunan Formulir General Consent di Puskesmas Kota Malang - Prima Soultoni Akbar (Kementerian Kesehatan Poltekkes Malang, 2024)
Lack of patient knowledge regarding rights and obligations at the Malang City Health Center. So many patients do not know what rights they have while receiving treatment at the health center and what obligations they have as patients that must be adhered to. The aim of this research is to determine the relationship between the level of patient knowledge and the use of general consent forms in Malang city health centers. The research design uses quantitative research with a cross sectional approach. Researchers divided groups into different treatments, namely using forms and not using forms, totaling 60 samples. The tool in this research is a questionnaire with a variable level of patient knowledge regarding the general consent form. Data analysis used the Independent T-Test. The research results showed that the level of knowledge of those using the form was higher than that of those not using the general consent form. The conclusion of this research is that there is a relationship between the level of knowledge and the use of general forms at the Malang City Health Center.